Navigating the Digital Divide: Common Problems with Telemedicine and How to Solve Them - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Navigating the Digital Divide: Common Problems with Telemedicine and How to Solve Them Keywords: Telemedicine problems, telehealth challenges, digital h...
Keywords: Digital Health; Diagnostics; Healthcare Innovation; Medical Ethics; Patient Care